Developing skill-based schools with the aim of training female students - Gulnoza Abdukodirovna, Qarshiboyeva; Rayimovich Abduqayumov , Asror; Nina Vasilievna , Goncharova; Selimovna Islyamova , Lenara; Saida Durdiyevna, Rakhimova; Abdukaxxarovna Azimova , Umida (Cadernos de Educação Tecnologia e Sociedade, 2024)
Today, the educational system is recognized as an important and fundamental tool in the comprehensive growth and development of countries, therefore, its growth, transformation, reform, and quantitative and qualitative improvement are among the most important issues of any country. Schools are among the most important periods of the educational system because they provide the basis for the formation of personality and the comprehensive development of individuals and are the most appropriate opportunity for education, learning, and the development of children's talents. If children do not learn the necessary skills at this age, the opportunity to compensate for this in the later stages of growth will be very difficult. In order to effectively implement the cooperative learning method, the cooperation of textbook authors, educational decision-makers, teachers, and parents is essential. Developing practical skills in students is very important. These skills help students make the best use of their course materials and also have more success in their daily lives. In the present study, an attempt has been made to introduce practical skills and active learning methods, their impact on student performance, and to examine solutions to improve students' practical skills. The present article was prepared using a mixed research method. Given the necessity of creating and developing learning opportunities for students in the classroom, school and outside of it, a skill-based approach and increasing the alignment and coordination of learning with individual and social needs, the skill-based homework plan was examined in the first year of elementary school. In this plan, part of the learning activities are carried out in the form of exercises to teach and learn basic skills such as reading, writing, mathematical knowledge, observing, speaking, listening, etc. in the classroom or school environment in the interaction and participation of the teacher and the student. Therefore, the purpose of this study is to investigate the effect of skill-based and creative homework on the learning rate of elementary school students. In this article, an attempt has been made to investigate the importance and role of skill-based homework on the learning rate of students using a descriptive-analytical method and library and field data collection methods, and finally, suggestions have been made for providing creative homework to increase student learning.